2018
DOI: 10.1292/jvms.17-0583
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of the efficacy of commercial and prototype PRRS subunit vaccines against an HP-PRRSV challenge

Abstract: The objective of this study was to compare the efficacy of a commercial porcine reproductive and respiratory syndrome (PRRS) subunit vaccine and a prototype PRRS II subunit vaccine against a highly pathogenic PRRS virus (HP-PRRSV) in pigs. Both vaccines were administered intramuscularly in 2 doses at 21 and 42 days of age, and the pigs were challenged intranasally with HP-PRRSV at 63 days of age. Pigs vaccinated with the prototype PRRS II subunit vaccine had significantly higher anti-PRRSV antibody titers, a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The subunit vaccine, also known as a biosynthetic subunit vaccine, is made by inserting specific-antigen-encoding genes into viruses or cells that are prone to proliferation to express effective specific antigens and purifying them [ 67 ]. Although they are safe and stable, their immunogenicity is usually low.…”
Section: Subunit Vaccinementioning
confidence: 99%
“…The subunit vaccine, also known as a biosynthetic subunit vaccine, is made by inserting specific-antigen-encoding genes into viruses or cells that are prone to proliferation to express effective specific antigens and purifying them [ 67 ]. Although they are safe and stable, their immunogenicity is usually low.…”
Section: Subunit Vaccinementioning
confidence: 99%
“…Currently, seven commercial MLV vaccines are used to control PRRS in China with their corresponding virus strains including VR2332, R98, JXA1-P80, HuN4-F112, GDr180, TJM-F92 and CH-1R (Cai et al, 2012;Charerntantanakul, 2012;Han et al, 2009;Leng, Li, Xia, He, & Wu, 2012;Tian et al, 2009;Yu et al, 2015). PRRS MLV vaccines can provide appreciable protection against genetically homologous PRRSV (Charoenchanikran et al, 2016;Duy et al, 2018;Sirisereewan et al, 2018). However, only partial protection was provided by MLV vaccines in preventing heterologous PRRSV strains infection (Bai et al, 2016;Wang et al, 2016;Zhou et al, 2017).…”
Section: Ns Nsmentioning
confidence: 99%
“…Numerous studies have demonstrated that the neutralizing antibodies induced by these two epitopes can effectively reduce the lethality of PRRSV infection in pigs and are, therefore, important targets for the development of subunit vaccines [17][18][19]. Although GP5 is considered to be an ideal target for the design of novel vaccines, some experimental vaccines based on the expression of the native GP5 protein, such as subunit vaccines, viral vector vaccines, DNA vaccines, and so on, often fail to induce higher neutralizing antibodies [18,[20][21][22][23][24][25]. Additionally, there is also a nonneutralizing decoy epitope (aa 27-31) located upstream of the neutralizing epitope GP5B (aa [37][38][39][40][41][42][43][44][45], which may hinder the recognition of the GP5B epitope and the subsequent development of neutralizing antibodies [15].…”
Section: Introductionmentioning
confidence: 99%